Racial differences and the role of neighborhood in the sequencing of marijuana and tobacco initiation among urban youth. Issue 4 (October 2016) - Green, Kerry M.; Johnson, Renee M.; Milam, Adam J.; Furr-Holden, Debra; Ialongo, Nicholas S.; Reboussin, Beth A.
Background: With patterns of initiation of tobacco and marijuana changing, there is increasing evidence that marijuana use may serve as an antecedent to tobacco use among adolescents. However, studies have not fully characterized the prevalence of these patterns among vulnerable youth and have rarely examined the factors that predict the sequencing of onset of tobacco and marijuana use. Methods: Utilizing longitudinal data from a sample of urban youth followed from age 6 to age 18, the authors identify the sequencing of initiation of tobacco and marijuana and test whether race and 5 neighborhood factors (i.e., perceived disorder, drug activity, drug access, exposure to violence, and exposure to violent victimization) predict onset sequencing. Results: Various sequencing patterns were observed, with 12.4% of the sample initiating marijuana use before tobacco use was initiated. In adjusted logistic regression models, black youth were 2.66 times as likely as whites to initiate marijuana before tobacco compared with initiating tobacco before marijuana ( P = .032). Youth with greater exposure to violent victimization were 3.89 times as likely to initiate marijuana first than initiate tobacco first ( P = .002). Other neighborhood factors were not statistically significantly associated with sequencing. Conclusions: Black youth and youth with greater exposure to victimization had an increased risk of initiating marijuana before tobacco, which suggests that this pattern may be rooted in specific risk factors. Substance use prevention efforts should consider taking into account that marijuana use may put certain youth at risk of initiating tobacco. Future research needs to monitor sequencing, as well as risk factors for and consequences of the various patterns, particularly since marijuana use and the mixing of tobacco and marijuana use are gaining acceptability in general populations.